Simultaneous trace gas measurements using two Fourier transform spectrometers at Eureka, Canada during spring 2006, and comparisons with the ACE-FTS - Fu, D.; Walker, K. A.; Mittermeier, R. L.; Strong, K.; Sung, K.; Fast, H.; Bernath, P. F.; Boone, C. D.; Daffer, W. H.; Fogal, P.; Kolonjari, F.; Loewen, P.; et al. (Atmospheric Chemistry and Physics, 2018)
The 2006 Canadian Arctic ACE (Atmospheric Chemistry Experiment) Validation Campaign collected measurements at the Polar Environment Atmospheric Research Laboratory (PEARL, 86.42° W, 80.05° N, 610 m a.s.l.) at Eureka, Canada from 17 February to 31 March 2006. Two of the ten instruments involved in the campaign, both Fourier transform spectrometers (FTSs), were operated simultaneously, recording atmospheric solar absorption spectra. The first instrument was an ABB Bomem DA8 high-resolution infrared FTS. The second instrument was the Portable Atmospheric Research Interferometric Spectrometer for the Infrared (PARIS-IR), the ground-based version of the satellite-borne FTS on the ACE satellite (ACE-FTS). From the measurements collected by these two ground-based instruments, total column densities of seven stratospheric trace gases (O 3 , HCl, ClONO 2 , HF, HNO 3 , NO 2 , and NO) were retrieved using the optimal estimation method and these results were compared. Since the two instruments sampled the same portions of atmosphere by synchronizing observations during the campaign and used consistent retrieval parameters, the biases in retrieved columns from the two spectrometers represent the instrumental differences. Mean differences in total column densities of O 3 , HCl, ClONO 2 , HF, HNO 3 , and NO 2 from the observations between PARIS-IR and the DA8 FTS are 2.8 %, −3.2 %, −4.3 %, −1.5 %, −1.9 %, and −0.1 %, respectively. Partial column results from the ground-based spectrometers were also compared with partial columns derived from ACE-FTS version 2.2 (including updates for O 3 ) profiles. Mean differences in partial column densities of O 3 , HCl, ClONO 2 , HF, HNO 3 , NO 2 , and NO from the measurements between ACE-FTS and the DA8 FTS are −5.9 %, −8.5 %, −11.8 %, −0.9 %, −6.6 %, −21.6 % and −7.6 % respectively. Mean differences in partial column densities of O 3 , HCl, ClONO 2 , HF, HNO 3 , NO 2 from the measurements between ACE-FTS and the PARIS-IR are −5.2 %, −4.6 %, −2.3 %, −4.7 %, 5.7 % and −11.9 %, respectively. This work provides further evidence of the reliability of ACE-FTS measurements from the first three years of on-orbit observations. Column densities of O 3 , HCl, ClONO 2 , and HNO 3 from the three FTSs were normalized with respect to HF and used to compare the time evolution of the chemical constituents in the atmosphere over Eureka during spring 2006.